2017
DOI: 10.1097/md.0000000000006090
|View full text |Cite
|
Sign up to set email alerts
|

An artificial neural network prediction model of congenital heart disease based on risk factors

Abstract: An artificial neural network (ANN) model was developed to predict the risks of congenital heart disease (CHD) in pregnant women.This hospital-based case-control study involved 119 CHD cases and 239 controls all recruited from birth defect surveillance hospitals in Hunan Province between July 2013 and June 2014. All subjects were interviewed face-to-face to fill in a questionnaire that covered 36 CHD-related variables. The 358 subjects were randomly divided into a training set and a testing set at the ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 35 publications
4
56
0
1
Order By: Relevance
“…We observed that maternal adverse emotions during pregnancy (OR = 2.650, 95% CI: 1.903~3.692) were the most important factor in the occurrence of CHD. This association was also observed in the studies of LI Huixia et al 18 . With the slowdown of Chinese economic growth, the major pressures of life and the gap between the rich and the poor, the fast pace of life and negative habits make psychological problems increasingly common 19 .…”
Section: Discussionsupporting
confidence: 80%
“…We observed that maternal adverse emotions during pregnancy (OR = 2.650, 95% CI: 1.903~3.692) were the most important factor in the occurrence of CHD. This association was also observed in the studies of LI Huixia et al 18 . With the slowdown of Chinese economic growth, the major pressures of life and the gap between the rich and the poor, the fast pace of life and negative habits make psychological problems increasingly common 19 .…”
Section: Discussionsupporting
confidence: 80%
“…We identified 31 studies published between 1990 and 2018 according to the inclusion criteria. Study selection was summarized in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the above paternal risk factors, there are also several studies concerned about other paternal risk factors, such as chronic disease, viral infection, etc. Paternal chronic disease was another risk factor for CHDs (OR = 4.87, 95% CI: 1.23‐19.24), according to the findings of Li's investigation . And paternal virus infection (OR = 2.46, 95% CI: 1.13‐5.35), antibiotics usage (OR = l0.04, 95% CI: 1.28‐78.45) may also increase the risk of CHDs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where several studies such as the one carried out by Li et al assessed the risk of heart attack utilizing an artificial neuron network. 22 Other studies employed machine learning in order to identify the risk of developing other diseases, such as colorectal cancer, 23 respiratory virus affinity, 24 melanoma, 25 mortality in smokers, 26 depression 1 or HIV transmission, 27 among others.…”
Section: Preventive Medicinementioning
confidence: 99%